Rural-urban migration in Bangladesh: an urban perspective - Mohit, Mohammad Abdul (Bangladesh Institute of Planners, 1990)
This paper provides an explanation to internal migration pattern within the urbanization process of Bnagladesh. The analysis has identified the weak attractiveness of urban centres with below 100,000 population to the migrants of Bangladesh. by contrast, the migration proneness of the larger urban centres has also become evident from the analysis. Therefore, a balanced distributuion of internal migration would require stregthening the economies of the small and medium sized urban centres so that potential migrants may be attracted to these towns.